The imperative of embedding sustainability in business: A model for transformational sustainable development. (28th March 2021) - Trollman, Hana; Colwill, James
Abstract: Sustainable development is the current strategic trajectory with transformative intent for complex global challenges including eradication of poverty, full social inclusion and prevention of ecological collapse. However, discourses related to the private sector emphasise economic and social development over the environmental components of sustainable development. Embedding sustainability is the related management imperative for business, supported by numerous frameworks, yet there is confusion about implementation in both literature and practice. This research addresses these issues with a mixed methods study combining a scoping literature review with a qualitative e‐Delphi study. The main findings are that the economic system constrains the embedding of sustainability in business; and that a paradigm shift towards ecocentric business models lacks support. The results are used to develop a novel model to aid transformational sustainable development that acknowledges the influences of the economic system in business whilst respecting social and ecological embeddedness.